Deciphering the molecular mechanism of enhanced tumor activity of the EGFR variant T790M/L858R using melanoma cell lines - Shao, Hanshuang; Wells, Alan (Frontiers in Oncology, 2023)
Introduction: The abnormal expression and mutagenesis of EGFR drives both development and progression of a multitude of human cancers. Further mutations within the tyrosine kinase region of the EGFR subsequently contribute to resistance to targeted drugs. What is not known is how these mutations affect progression-related behaviors of cancer cells. Methods: The mutagenesis of EGFR T790M, L858R and T790M/L858R was performed via oligo primers-guided polymerase chain reaction (PCR). GFP tagged mammalian expression vectors were constructed and confirmed. Stable melanoma cell lines WM983A expressing WT or mutant EGFRs were generated for determining the functions of WT and mutant EGFRs in migration, invasion, and resistance to doxorubicin. Immunoblotting and immunofluorescence were performed to detect the transphosphorylation and autophosphorylation of WT and mutant EGFRs and other molecules. Results: EGFR mutant T790M/L858R showed significantly higher basal autophosphorylation in melanoma cell line WM983A. Overexpression of WT EGFR significantly enhanced the protein level of E-cadherin (E-cad) via upregulating its mRNA. In contrast, L858R significantly downregulated E-cad. Biological activity assays show that T790M/L858R presented significant enhancement in vitro in invasion and migration, while WT and T790M moderately inhibit invasion and migration. Enhanced invasion and migration by T790M/L858R required the downstream signaling pathways through Akt and p38. T790M/L858R dramatically triggers phosphorylation of actin-cross linking protein alpha-actinin4 in the absence of EGF. This double mutant also conferred resistance to a general chemotherapy doxorubicin through Akt but not p38 signaling pathway. Conclusion: These findings suggest that T790M/L858R not only confers enhanced therapeutic resistance in cancer cell lines but also may promote tumor metastasis via its boosted downstream signaling pathways and/or direct phosphorylation of other key proteins.